ANALISIS KELAYAKAN INVESTASI TEKNOLOGI ROBOTIKA PADA LINI PRODUKSI PT. A - Hendriana, Dadang; Putra, Aditya Eka Pramana; Kusumadewi, Intan (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2021)
This research purpose is analyzing investment feasibility on manufacture company related management plan. Company investment project in 2019 is robotic technologies application in production line assembly, robotic installation theme for 2019 is Six Axis Robot Tank Welding. Related this investment activity, required analyzing investment feasibility due avoiding finance loss after investment. Analyzing observing method for knowing feasibility value by using 3 aspect, base on stake holders concept (Suliyanto, 2013). Feasibility aspect during reasearch activity are market aspect , teknical & operation aspect & finance aspect, each aspect contain feasibility parameter for make judgement investment feasibility value on investment project. Key words: Six Axis Robot, market aspect, technical & operation aspect, financial aspect